Analysis of The Influence of Organizational Commitment and Work Discipline on Employee Performance with Job Satisfaction as An Intervening Variable - Aliyah, A.Nabilah; Sumardi; Reni, Andi (PT. Maju Malaqbi Makkarana, 2023)
The primary objective of this research is to examine and assess the impact of work dicipline and organizational commitment on employee performance. In an endeavor to enhance individual and group employee performance, specific standards of responsibility have been instituted for each individual in the execution of their duties. Typically, employees exhibiting a high level of competence in their roles suggest that their success in the work environment has been optimized. Consequently, this study was conducted to elucidate the interrelations between work motivation, job satisfaction, organizational commitment, and employee performance within the context of the Regional Drinking Water Company of Makassar City (PDAM Makassar City).The research involved the collection of data from 107 employees of the Makassar City Regional Drinking Water Company to empirically test the proposed research model, utilizing WarpPLS 7.0 modeling software. The findings of the study reveal that there is a statistically significant influence of organizational commitment and work discipline, both individually and collectively, on job satisfaction and employee performance. Additionally, a discernible impact of job satisfaction on employee performance was identified, and an indirect influence of organizational commitment and work discipline variables on performance was observed through their impact on job satisfaction